Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Kantor Shopee Express Kediri - Erlinda Ramadhani; Moch. Saleh Udin; Taufik Akbar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This research aims to determine the influence of work discipline, work environment, work motivation both partially and simultaneously on employee performance at the Shopee Express Kediri Office. The population in this study was office and operational employees at the Shopee Express Kediri Office, totaling 35 people. The sample in this research was obtained using a saturated sampling technique with a sample size of 35 respondents. Data sources were obtained by means of observation, interviews, questionnaires and documentation. This research data measurement uses a Likert scale. The analysis technique uses multiple linear regression analysis with the SPSS IBM 26 application. The results of this research show that the work discipline variable has a significant effect on employee performance. Work environment variables are significant on employee performance. The work motivation variable does not have a significant effect on employee performance. And the variables of work discipline, work environment and work motivation simultaneously have a significant effect on employee performance.